Global Trends in Health and Communication Research: A Bibliometric Analysis from the Scopus Database (1995–2025) - Febryanti, Ade (International Journal of Health Sciences, 2025)
The field of health and communication has experienced significant growth over the past three decades, driven by the increasing integration of digital technologies in public health and the demand for effective health information dissemination. This study aims to explore global trends in health and communication research through a bibliometric analysis of publications indexed in the Scopus database from 1995 to 2025. Using bibliometric indicators such as publication volume, authorship patterns, institutional and country collaborations, and keyword co-occurrence, this research identifies major contributors, thematic developments, and emerging research fronts in the field. The study used bibliometric analysis of 210 publications in the Scopus database from 1995 to 2025. Publication data was selected using the keyword "health AND communication." Data processing was conducted by co-occurrence between keywords and data presentation with overlay visualization. The results of data processing with VosViewer and R-Studio revealed shifts in research topics in 1995 to 2025. The findings reveal an upward trend in scholarly output, with a notable concentration of publications originating from high-income countries. Furthermore, the analysis highlights the growing importance of interdisciplinary collaboration and digital health themes. This study provides valuable insights for researchers, policymakers, and institutions seeking to understand the evolution of health communication research and to identify gaps and opportunities for future exploration.